Recent Progress in Anisotropic 2D Semiconductors: From Material Properties to Photoelectric Detection. Issue 16 (17th July 2021) - Wei, Liubo; Li, Yanran; Tian, Changfa; Jiang, Jie
Abstract : The widespread implementation and rapid growing development of emerging sensor systems has posed stringent performance requirements on high‐performance photoelectric detection. Therefore, researchers are committed to finding a new kind of semiconductors with faster response time, higher sensitivity, and better stability. Nowadays, anisotropic 2D materials have drawn great attentions in photoelectric detection due to their unique crystal structures and optical absorption properties. These properties make them possible to detect a wide spectrum from ultraviolet to infrared, which provides a good choice for photoelectric detection under complex conditions. Herein, the various anisotropic 2D materials with intriguing physical properties and their device applications for optoelectronic detection are reviewed. Abstract : Herein, the various photoelectric detectors based on anisotropic 2D materials are summarized. First, the crystal structure and preparation method of anisotropic 2D materials are introduced. Then, the Raman scattering on in‐plane anisotropic layered materials are discussed. Finally, different high‐performance polarization‐sensitive photodetectors based on anisotropic 2D materials are introduced.